2021
DOI: 10.1161/jaha.120.019051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morbid Obesity and Obesity Phenotype on Outcomes After Transcatheter Aortic Valve Replacement

Abstract: Background There is a paucity of outcome data on patients who are morbidly obese (MO) undergoing transcatheter aortic valve replacement. We aimed to determine their periprocedural and midterm outcomes and investigate the impact of obesity phenotype. Methods and Results Consecutive patients who are MO (body mass index, ≥40 kg/m 2 , or ≥35 kg/m 2 with obesity‐related comorbidities; n=9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Two studies found BMI as inversely associated to mortality, while visceral adiposity as independent risk factor for postoperative mortality. 20,21 Those findings confirm the suboptimal accuracy of BMI as trait for MetS. Opposite to the surgical group, in our series we found that MetS was not associated with worst postoperative outcomes in the TAVR subgroup.…”
Section: Discussionsupporting
confidence: 82%
“…Two studies found BMI as inversely associated to mortality, while visceral adiposity as independent risk factor for postoperative mortality. 20,21 Those findings confirm the suboptimal accuracy of BMI as trait for MetS. Opposite to the surgical group, in our series we found that MetS was not associated with worst postoperative outcomes in the TAVR subgroup.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies investigated the effect of specific risk factors (i.e., diabetes / obesity) (19) in patients undergoing TAVR, but none focused on MetS. Two studies found BMI as inversely associated to mortality, while visceral adiposity as independent risk factor for post-operative mortality (20,21). Those findings confirm the suboptimal accuracy of BMI as trait for MetS.…”
Section: Discussionmentioning
confidence: 98%
“…Over recent years, TAVI has been used as an alternative to surgical aortic valve replacement for patients deemed to be at high surgical risk. Studies, however, have demonstrated that TAVI in the younger morbidly obese patient group compared with normal‐weight counterparts is associated with an increased risk of major vascular complications (6.6% vs. 4.3%; p = .0430) and a lower device success rate (84.4% vs. 88.1%; p = .038) 75 . When comparing TAVI to an open approach, a retrospective analysis carried out in 284 obese patients found that there was no difference in mortality at 30 days (5.2% vs. 3.2%; p = .41) and the 5‐year survival was higher in the surgical aortic valve group compared with the TAVI group (71.8% vs. 52.8%; p = .0046) 64 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies, however, have demonstrated that TAVI in the younger morbidly obese patient group compared with normal-weight counterparts is associated with an increased risk of major vascular complications (6.6% vs. 4.3%; p = .0430) and a lower device success rate (84.4% vs. 88.1%; p = .038). 75 When comparing TAVI to an open approach, a retrospective analysis carried out in 284 obese patients found that there was no difference in mortality at 30 days (5.2% vs.…”
Section: Tavi Versus Open Approachmentioning
confidence: 99%